Relationship Between Government Expenditures on Health and Residents' Consumption: New Evidence From China Based on the Bootstrap Rolling-Window Causality Test - Jiang, Ting-Yu (Frontiers in Public Health, 2021)
This paper explores necessity to expand government expenditure on health from the perspective of promoting residents' consumption. It employs the bootstrap full- and sub-sample rolling-window Granger causality tests to investigate the mutual causal influence between government expenditure on health and residents' consumption. It finds that government expenditure on health has positive impact on residents' consumption in some periods while negative impact in other periods. The positive effect from government expenditure on health to residents' consumption reveals that Chinese governments at all levels should continue to increase government expenditure on health, narrow the gap with developed countries’ medical and health investment, directly reduce residents’ current medical expenses and increase their immediate consumption. Whereas, this opinion cannot always be held because the negative impact from government expenditure on health to residents' consumption also exists. The paper shows that the government should improve the efficiency of the use of health expenditure; effectively shorten the time lag of government health fiscal policies and promote the positive effect of government health expenditure on residents' consumption.